PENULISAN SURAT EDARAN DAN SURAT PENGUMUMAN DINAS PENDIDIKAN KABUPATEN KUBU RAYA - Rohana, Siti; Sulissusiawan, Ahadi; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to describe the writing of the circular and the notice of Kubu Raya District Education Office by Minister of National Education Republic of Indonesia Number 42 of 2006 on the use of the form / layout of letters, parts of letters, and the language of the letter. The method used is descriptive method. The data source of this research is to document the circular and the notice of the Department of Education Kubu Raya. Data collection techniques used is documentation. The results of data analysis on aspects of builders circulars and announcements covering letter writing letterhead, opening mail, letter, cover letters, and the language of the letter can be concluded that the writing circular and the notice of Kubu Raya District Education Office in 2008 to 2010 have not shown optimal results. In this case, aspects that need to be considered, especially aspects of the form of letters, parts of the letter (letterhead, opening mail, letter and cover letter), and the language letter. Keywords: Circular, Letter Announcements, Permendiknas.